Bacteria in Agrobiology: Crop Productivity - Maheshwari, Dinesh K.; Maheshwari, Dinesh K.; Saraf, Meenu.; Saraf, Meenu.; Aeron, Abhinav.; Aeron, Abhinav. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The future of agriculture greatly depends on our ability to enhance productivity without sacrificing long-term production potential. The application of microorganisms, such as the diverse bacterial species of plant growth promoting rhizobacteria (PGPR), represents an ecologically and economically sustainable strategy. The use of these bio-resources for the enhancement of crop productivity is gaining importance worldwide. Bacteria in Agrobiology: Crop Productivity focus on the role of beneficial bacteria in crop growth, increased nutrient uptake and mobilization, and defense against phytopathogens. Diverse group of agricultural crops and medicinal plants are described as well as PGPR-mediated bioremediation leading to food security.